(3GdebJQM aj GdeUWdM aj GdLOds - (3GdHQhj , eMeO Hf eMeO Hf eMeO Hf SYO Hf YHO Gddg, CHh efUhQ,J (B567 (3g` s
(3ChdgG (B:s
(3bGd GdEeGe GdLdjd CHh efUhQ GdHQOi QVi Gddg Yfg (B: (3GdMeO ddg GdPi NUfG HGdYbd hGdfWb hHYO abO SCdfi HYV GdCFeI Cf CUfa dg HYV eG JbQQ Ydjg GdEUWdGM ai efGXQGJ Gdabg s
(3BNQgG (B:s
(3gPG JeGe GdebJQM ai GdeUWdM hdbO hajJ Ef TGA Gddg ajg HVHW GdbhGYO GdcdjI hUdi Gddg Ydi eMeO NGJe GdfHjjf hSde JSdjekG s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B24 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B279s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eYGQVI Ydi fSNI GdeDpqdas
Keywords: (3GdadSaI hGdefWbs